Evolution of influenza and acute respiratory infections in the Republic of Moldova during the 2014/15-2022/23 seasons - DRUC, Alina (One Health & Risk Management, 2024)
Introduction. Influenza-like illness (ILI), Acute Respiratory Infections (ARI) and Severe Acute Respiratory Infections (SARI) are the most common infectious diseases globally, accounting for up to 95% of infectious diseases in some countries. They cause severe forms every year especially in at-risk groups. Material and methods. The descriptive-retrospective epidemiological study analyzed morbidity by ILI, ARI and SARI and laboratory results in the presence of influenza viruses during the 2014/2015-2022/2023 seasons. Results. ILI has been of low to medium intensity except for 2 seasons and ARI has been of very high intensity in one season. ILI, ARI and SARI primarily affected children aged 0-14 years. During the 9 seasons (exception 2020/2021) influenza virus types A(H1N1)pdm09, A(H3N2) and B have been identified, with the percentage of positives decreasing considerably in the last 2 seasons. During the period under review, each influenza virus dominated, and in 3 seasons 2-3 virus types co-dominated. Genetic characterization of the identified strains demonstrated that influenza viruses fully fit the phylogenetic tree constructed in the nominated period, do not differ antigenically from strains identified in other regions of the northern hemisphere and are susceptible to antivirals. Conclusions. The national surveillance system of ILI, ARI and SARI makes it possible to monitor the evolution of the epidemic process in real time and geographic space and facilitates prompt intervention with control and response measures.